Epilepsy care cascade, treatment gap and its determinants in rural South Africa. (August 2020) - Wagner, Ryan G.; Kabudula, Chodziwadziwa W.; Forsgren, Lars; Ibinda, Fredrick; Lindholm, Lars; Kahn, Kathleen; Tollman, Stephen; Newton, Charles R.
Highlights: Most people with active convulsive epilepsy in rural South Africa are diagnosed. Most individuals diagnosed have some blood level of anti-seizure medication. Most individuals do not have optimal levels of medication. The epilepsy treatment gap is high in rural South Africa, especially in children. Identifying the epilepsy care cascade may better allow for targeting of interventions. Abstract: Purpose: The percentage of people who are diagnosed with epilepsy (diagnostic gap), access, receive and adhere (treatment gap) to anti-seizure medication (ASM) in low- and middle- income countries remains low. We explored the epilepsy care cascade, measured the diagnostic and treatment gaps, and examined socio-demographic factors associated with adherence to ASMs in rural South Africa. Methods: Utilizing a population-based cohort of 311 people with active convulsive epilepsy (ACE) residing in rural northeastern South Africa, a questionnaire was administered to examine associations between demographic and socioeconomic factors and the epilepsy treatment gap. Blood was taken to measure levels of ASMs. Results: Of the 311 individuals diagnosed, 93 % of individuals reported being previously told they had epilepsy and 94 % reported previously attending a health facility for their epilepsy. ASMs were detected in 138 individuals (76 %) and optimal levels were detected in 67 individuals, resulting in a treatment gap of 63 % (95 % confidence interval [95 %CI]: 56 %–70 %). Self-reported specificity of ASM use was 23 % (95 %CI: 12–39 %) and individuals ≥18 years were significantly more likely to report taking ASM than children and were significantly (p = 0.011) more likely to be adherent. Conclusion: Most people with epilepsy in rural South Africa had been previously diagnosed with epilepsy and had accessed care for epilepsy, yet the level of ASM adherence remained low, significantly lower amongst children. Understanding ways of improving knowledge of and adherence to ASM in rural South Africa is necessary, especially amongst children. The epilepsy care cascade can be useful in identifying gaps in care and targeting interventions to reduce these gaps.